ChemInform Abstract: The Phosphinoboration Reaction. Issue 25 (5th June 2015) - Daley, Erika N.; Vogels, Christopher M.; Geier, Stephen J.; Decken, Andreas; Doherty, Simon; Westcott, Stephen A.
Abstract: The single P—B bond of novel phosphinoboronate ester (II) is highly reactive and readily undergoes addition to C=O and C=N bonds, respectively.